Public Library: Efforts to Increase Reading Interest of Orphans at the Taqwa Al-Kausar House Foundation, Sidoarjo: Perpustakaan Umum : Upaya Peningkatan Minat Baca Anak Panti Di Yayasan Rumah Taqwa Al-Kausar Sidoarjo - Setiawan, Hamzah; Rahmawati, Yunianita; Sumarmi, Wiwik; Jakaria, Ribangun Bamban; Kusumawardani, Paramitha Amelia (Universitas Muhammadiyah Sidoarjo, 2022)
The public library of the Taqwa al-Kausar house foundation aims to provide facilities for children's homes and the surrounding community in providing quality reading materials as a result of the many reading interests owned by children's homes, but in its management which includes book inventory, library management systems , the process of borrowing and measuring, is carried out by recording and only done with simple recording, so that many books are available, the management system is not good, the existing books are not found and it is difficult to manage the children's home or the community has borrowed and did not return it, apart from There are many books that are not registered and do not have a book inventory system, meanwhile they do not have a book inventory system, meanwhile library management for librarian managers and staff has never been carried out. So from these problems the solutions to be offered are (1) Building an online-based library information system, (2) Library management training, (3) Provision of online-based library information system support facilities, (4) librarian training. So that with professional library management, you will be able to maximize the potential of the Rumah Al-Kausar Foundation public library which is able to provide stemulus in an effort to increase the love of reading and the professionalism of management and administrators in the future will be a reference for independent public libraries in Sidoarjo.